1999
DOI: 10.1287/mnsc.45.5.722
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Utilization of Workers Whose Capabilities Differ

Abstract: This paper develops a model for allocating cross-trained workers at the beginning of a shift in a multidepartment service environment. It assumes departments are trying to maximize objective functions that are concave with respect to the number of workers assigned. Worker capabilities are described by parameters that range from zero to one, with fractional values representing workers who are less than fully qualified. The nonlinear programming model presented is a variant of the generalized assignment problem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 22 publications
6
97
0
10
Order By: Relevance
“…Substitution possibilities can also be obtained through cross-training. Campbell (1999) investigates the impact of the cross-utilisation of employees for different levels of demand variability (uncertainty of demand) and employee cross-training. Similarly, Olivella and Nembhard (2016) determine the optimal level of cross-training in work teams to deal with variations in the demand mix and employee availability.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Substitution possibilities can also be obtained through cross-training. Campbell (1999) investigates the impact of the cross-utilisation of employees for different levels of demand variability (uncertainty of demand) and employee cross-training. Similarly, Olivella and Nembhard (2016) determine the optimal level of cross-training in work teams to deal with variations in the demand mix and employee availability.…”
Section: Literature Overviewmentioning
confidence: 99%
“…In this respect it touches on a significant body of literature that treats the problem of cross-trained workers from various perspectives. Campbell and Diaby (2002) develop heuristics for the model of Campbell (1999) which assigns cross-trained workers across different departments at the beginning of a shift. The departmental utility function is non-linear and the resulting model can be viewed as a variant of the GAP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second-stage is a recourse on realized demands. Sayın and Karabatı (2007) also build a framework based on the non-linear nature of the departmental objective function of Campbell (1999). They propose a two-stage model, where two objective functions, departmental utility and skill improvement, are considered in the assignment of cross-trained workers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al (1994). Also, the model addresses the issue of workforce allocation in order to meet job site demands, which was studied by Campbell (1999), Beaumont (1997), and Thompson (1995).…”
Section: Use Of Relevant Optimization Techniques Outside Constructionmentioning
confidence: 99%
“…This restriction is based on previous studies which indicated limited benefits for cross-training workers in more than one additional skill (Gomar 1999, Campbell 1999, and Burleson et. al 1998.…”
Section: Main Assumptionsmentioning
confidence: 99%